A modern study of the kinetics and mechanism of the cementation of gold - M. J. Nicol; E. Schalch; P. Balestra (The Southern African Institute of Mining and Metallurgy, 1979)
A detailed fundamental study has been made of the various factors that influence the partial reactions comprising the electrochemical model of the cementation of gold from cyanide solutions by zinc. The effects of cyanide concentration, pH, agitation, additions of lead, and the presence of various impurity ions on both the anodic dissolution of zinc and the cathodic reduction of gold have been investigated. The results are used to explain the influence of these variables on the rate of cementation, and possible implications of this work for plant practice are discussed.